Chalmersa osobliwa teoria świadomości - MIŁKOWSKI, Marcin (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
In this paper, I argue that the supposedly new theory of consciousness proposed recently by David Chalmers is very close to classical functionalism. Indeed, it treats some of the controversial assumptions of functionalism as naturally necessary. This is, however, very unfortunate, as they lead to numerous tensions in his view. In the fi rst part, I analyze the functionalist theory of independence of complex organizations from their material realization. Then, I sketch several functionalist theories of consciousness as a background for Chalmers’ own theory. Pace Chalmers, some of them are theories of qualities of experience as well. In the third part, I show that Chalmers, instead of rejecting the functionalist independence claims, retains them as “the principle of organizational invariance”. This, however, leads to the very problems that made functionalism a bad candidate for a theory of consciousness (at least according to Chalmers’ own view). Lastly, I argue that he has to either view the hard problem of consciousness as pseudo-problem or reject his own theory as insuffi cient, as it is mere rebranding of classical computational functionalism and has no serious answer to the hard problem of consciousness.